Card collection: An examination of whether yellow and red cards affect base salary under Major League Soccer`s salary cap - Lussier, J.; Kim, J. W.; Magnusen, M. J.; Kim, K. T. (International Journal of Sports Science & Coaching, 2022)
We examine the effect of card (yellow and red) collection on player remuneration under the salary cap in Major League Soccer (MLS). The data contain 1478 observations of 731 players under contract between 2015 and 2019. Though the number of yellow cards a player collected had a significant impact, the number of red cards collected was not found to be a significant factor. On average, when a player has accumulated more than eight yellow cards over the course of the regular season, his salary was dropped substantially. If a player receives more than two red cards, his salary was decreased. A key result was that players who were aggressive without crossing the line to the point of being ejected from the field of play received comparatively higher salaries.